Ligninolytic enzymes production by Dichostereum sordulentum cultures in the presence of Eucalyptus bark as a natural laccase stimulator - Botto, Emiliana; D’annibale, Alessandro; Petruccioli, Maurizio; Galetta, Alejandra; Martínez, Sebastian; Bettucci, Lina; Menéndez, Maria Pilar (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
A strain of a fungal species, i.e., Dichostereum sordulentum, not yet isolated from either Uruguay or decayed Eucalyptus spp. wood, was investigated for its ability of producing extracellular ligninolytic enzymes. To this aim, the strain was grown on a N-rich liquid medium added with either bark or wood Eucalyptus dunnii sawdust. The former additive was more effective than the latter instimulating laccase leading to a production of 4.78 IU mL-1 which was further enhanced by the concomitant presence of 80 ppm CuSO4 (6.56 IU mL-1). The two order of magnitude higher proanthocyanidin content in bark than in wood suggests that this fraction might be responsible for the higher stimulatory effect of the former on laccase production.